2021
DOI: 10.1002/ana.26168
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Hippocampal Network Connectivity in Alzheimer's Disease

Abstract: Objective The hippocampus is connected to 2 distinct cortical brain networks, the posterior–medial and the anterior–temporal networks, involving different medial temporal lobe (MTL) subregions. The aim of this study was to assess the functional alterations of these 2 networks, their changes over time, and links to cognition in Alzheimer's disease. Methods We assessed MTL connectivity in 53 amyloid‐β–positive patients with mild cognitive impairment and AD dementia and 68 healthy elderly controls, using resting‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 64 publications
(211 reference statements)
5
28
0
Order By: Relevance
“…In regard to the anterior HC, we observed that redundancy levels were not affected by A β -status. This finding is in-line with the reported distinct vulnerability of anterior and posterior hippocampal systems to AD pathology (Dautricourt et al, 2021; Maass et al, 2019), such that the posterior networks are selectively targeted by A β pathology while anterior networks are vulnerable to tau pathology (Adams, Maass, Harrison, Baker, & Jagust, 2019; Maass et al, 2019). Though there were no amyloid effects on anterior HC redundancy, we did find evidence of diagnostic differences, particularly when the global redundancy measure was segregated into direct and indirect components.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In regard to the anterior HC, we observed that redundancy levels were not affected by A β -status. This finding is in-line with the reported distinct vulnerability of anterior and posterior hippocampal systems to AD pathology (Dautricourt et al, 2021; Maass et al, 2019), such that the posterior networks are selectively targeted by A β pathology while anterior networks are vulnerable to tau pathology (Adams, Maass, Harrison, Baker, & Jagust, 2019; Maass et al, 2019). Though there were no amyloid effects on anterior HC redundancy, we did find evidence of diagnostic differences, particularly when the global redundancy measure was segregated into direct and indirect components.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the posterior HC is strongly connected to PM regions, including the posteriomedial entorhinal cortex, parahippocampal cortex, retrosplenial cortex, posterior cingulate cortex (PCC), and precuneus and underscores processing contextual information of episodic memory (Kahn et al, 2008; Libby et al, 2012; Ranganath & Ritchey, 2012). The AT and PM systems are further differentiated by their selective susceptibility to AD pathology, as regions of the AT network are most burdened by tau pathology while the PM network is most vulnerable to A β pathology (Dautricourt et al, 2021; Maass et al, 2019). The susceptibility of the PM system to A β pathology is supported by the extant AD literature, which demonstrates that major hubs of the PM, including the precuneus and posterior cingulate cortex, that show a high degree of connectivity throughout the brain (van den Heuvel & Sporns, 2013), are some of the earliest regions to exhibit and drive A β pathology deposition (Buckner, Andrews-Hanna, & Schacter, 2008; Palmqvist et al, 2017; Pasquini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Because increased FC was associated with Aβ pathology and neurodegeneration, it suggests that hyperconnectivity is dysfunctional rather than compensatory. A pathological increase in FC between the entorhinal cortex and hippocampus at rest is supported by previous findings 38, 40, 46, 47 . For example, studies comparing resting state FC between patients with MCI or AD with elderly controls have found increased FC between entorhinal cortex and the hippocampus, particularly with the hippocampal head 38 , consistent with our results.…”
Section: Discussionsupporting
confidence: 86%
“…Then, current research is limited to the analysis of the rs-fMRI data collected in a single time period and does not verify multiple time periods. In the future, we will study the longitudinal trajectories ( Dautricourt et al, 2021 ) of functional brain dynamics over multiple time periods. Last but not least, although this article interprets the temporal dynamics of the functional brain network well and has obtained good experimental results, a correlation analysis with behavioral data should be performed in the future.…”
Section: Discussionmentioning
confidence: 99%